Challenges Faced in The Application of Reflective Practice on The Public Health Teaching and Learning Process by The Lecturers in Selected Universities in Lusaka and Copperbelt Provinces of Zambia - Namonje, Elizabeth; Halwiindi, Hikabasa; Zyambo, Cosmas; Simui, Francis; Muleya, Gistered (Advances in Social Sciences Research Journal, 2023)
This study explored challenges faced in the application of reflective practice on the public health teaching and learning process by the lecturers in selected universities in Lusaka and Copperbelt Provinces of Zambia. The study rids on a case study design to generate evidence on challenges faced. Data was collected from a total sample of 32 participants. The study found that too much workload by lecturers, large number of students in class, limited time with a semester system, limited resources for teaching staff and students, shortage of teaching staff and lack of teaching qualifications and experience amongst teaching staff were among challenges that affected lecturers’ ability to reflect on their teaching . Equally, it was found that lecturers refusing to be evaluated, cultural lag among older lecturers and differences in backgrounds among teaching staffs had a negative implication on lecturers’ ability to reflect on their teaching. The study concluded that despite reflective teaching practice being an important strategy for promoting quality teaching and learning, higher learning institutions have not paid much attention on impediments to reflective teaching. Therefore, the study recommends that Education standards officers should continue to maintain standards in Universities and Colleges to control over enrolments and overcrowding in classes so that the lecturers can teach efficiently and effectively so that students can benefit fully from the lecturers.